Effectiveness of Esports Sponsorship in Mobile Legends Professional League on Brand Association and Purchase Intention - Jeshen Oktavian Nathanel; Bambang Widjanarko Otok (Riviera Publishing, 2025)
The esports industry has experienced significant growth in recent years, attracting the attention of various sponsors to utilize these platforms in achieving their business goals. This study aims to analyze the effectiveness of esports sponsorship in the Mobile Legends Professional League (MPL) on brand associations and consumer purchase intentions. Using a quantitative approach and Structural Equation Modeling (SEM) techniques through SmartPLS, data was collected from 160 respondents who are active in the esports community in Indonesia. The results showed that positive attitudes towards sponsors (?=0.461, p<0.001) and sincerity of sponsorship motives (?=0.177, p=0.039) had a significant effect on brand association. Sponsor-event suitability (?=0.241, p=0.030) and activity engagement (?=0.240, p=0.004) were also shown to strengthen brand associations. For purchase intent, attitudes towards sponsors (?=0.391, p<0.001), sincerity of motives (?=0.223, p=0.013), and activity involvement (?=0.197, p=0.037) showed significant influences. This research model was able to explain 88.3% of brand association variance and 85% of purchase intention variance. These findings provide strategic insights for esports sponsors to optimize their investments through an authentic and relevant approach to the target audience.